A Bidirectional Flow Joint Sobolev Gradient for Image Interpolation. (25th May 2013) - Zhan, Yi; Li, Sheng Jie; Li, Meng
Abstract : An energy functional with bidirectional flow is presented to sharpen image by reducing its edge width, which performs a forward diffusion in brighter lateral on edge ramp and backward diffusion that proceeds in darker lateral. We first consider the diffusion equations as L 2 gradient flows on integral functionals and then modify the inner product from L 2 to a Sobolev inner product. The experimental results demonstrate that our model efficiently reconstructs the real image, leading to a natural interpolation with reduced blurring, staircase artifacts and preserving better the texture features of image.